Opportunities, resources, and techniques for implementing genomics in clinical care. Issue 10197 (10th August 2019) - Manolio, Teri A; Rowley, Robb; Williams, Marc S; Roden, Dan; Ginsburg, Geoffrey S; Bult, Carol; Chisholm, Rex L; Deverka, Patricia A; McLeod, Howard L; Mensah, George A; Relling, Mary V; Rodriguez, Laura Lyman; et al.
Summary: Advances in technologies for assessing genomic variation and an increasing understanding of the effects of genomic variants on health and disease are driving the transition of genomics from the research laboratory into clinical care. Genomic medicine, or the use of an individual's genomic information as part of their clinical care, is increasingly gaining acceptance in routine practice, including in assessing disease risk in individuals and their families, diagnosing rare and undiagnosed diseases, and improving drug safety and efficacy. We describe the major types and measurement tools of genomic variation that are currently of clinical importance, review approaches to interpreting genomic sequence variants, identify publicly available tools and resources for genomic test interpretation, and discuss several key barriers in using genomic information in routine clinical practice.